Binder-Free Hexagonal Boron Nitride Nanosheets (BNNSs) as Protective Coatings for Copper, Steel, and Wood: A Review - Muhammad Faheem Maqsood; Syed Muhammad Zain Mehdi; Arslan Ashraf; Umair Azhar; Naseem Abbas; Muhammad Asim Raza; Mohammed Amer (Crystals)
Hexagonal boron nitride (h-BN) has emerged as a promising dielectric material for protecting metallic substrates such as copper and steel under ambient conditions. The layered structure of h-BN offers significant potential in preventing the oxidation and corrosion of these substrates. Due to their impermeability, boron nitride nanosheets (BNNSs) do not form a galvanic cell with the underlying metals, enhancing their effectiveness as protective coatings. BNNSs are both thermally and chemically stable, making them suitable for coatings that protect against environmental degradation. Additionally, BNNSs have demonstrated excellent fire resistance, hydrophobicity, and oxidation resistance when applied to wood, functioning as a binder-free, retardant coating that remains effective up to 900 °C in air. This review focuses on the anti-corrosion properties of BNNSs, particularly on copper and steel substrates, and discusses various methods for their application. This article also discusses future perspectives in this field, including the innovative concept of wooden satellites designed for short- and long-term missions.